Two Decades of Nursing Home Compare: What Have We Learned?. (August 2021) - Tamara Konetzka, R.; Yan, Kevin; Werner, Rachel M.
Approximately two decades ago, federally mandated public reporting began for U.S. nursing homes through a system now known as Nursing Home Compare. The goals were to provide information to enable consumers to choose higher quality nursing homes and to incent providers to improve the quality of care delivered. We conduct a systematic review of the literature on responses to Nursing Home Compare and its effectiveness in meeting these goals. We find evidence of modest but meaningful response by both consumers and providers. However, we also find evidence that some improvement in scores does not reflect true quality improvement, that disparities by race and income have increased, that risk-adjustment of the measures is likely inadequate, and that several key domains of quality are not represented. Our results support moderate success of Nursing Home Compare in achieving intended goals but also reveal the need for continued refinement.